Hiccup as an uncommon symptom of pneumonia - Paulina Terlecka; Anna Grzywa-Celińska; Justyna Emeryk-Maksymiuk; Katarzyna Szmygin-Milanowska; Janusz Milanowski (Kazimierz Wielki University, 2017)
Hiccup is a symptom resulting with uncontrolled contractions of the diaphragm and external intercostals muscles with inspiration and with simultaneous sudden closure of the glottis, that produces specific "hic" sound. Depending on the time of duration, hiccup can be classified as acute (up to 48h), chronic (48h to 1 month) and persistent (lasting longer than one month). The exact pathophysiology of this symptom still remains unknown, though it is well known, that short-term episodes of hiccup are mainly caused by oesophagus and stomach diseases (gastric and duodenal ulcers, gastritis, gastro-oesophageal reflux) or alcohol consumption. Other reasons of this phenomenon include the diseases with the stimulation of the vagus nerve or conditions with diaphragm irritation. It can be also psychogenic or resulting from central nervous system diseases. Short term episodes of hiccup happen to every person and do not cause any concern. Chronic hiccups can lead to significant worsening of quality of life including fatigue, nutritional restrictions, dehydration, weight loss, insomnia, respiratory disorders, depression or even suicidal thoughts.             We present an interesting case with diagnostic and therapeutic procedures in a 65-year-old smoker, who was hospitalized in our Department because of pneumonia, with persistent hiccup as an additional complaint considerably deteriorating his quality of life.